Tantangan Minat Baca di Masyarakat Desa: Implementasi Program Sahabat Buku sebagai Solusi Literasi - Fuza Fadlilatulhaq; Aditia Abdurachman; Rida Sri Astuti; Fariz Moh Ihsan (LPPI UMN AL WASHLIYAH, 2025)
Literacy problems remain a serious challenge in Indonesia, particularly in rural areas such as Sindangraja Village, Jamanis District, Tasikmalaya Regency. Low reading interest, limited access to reading materials, and the lack of shared literacy spaces hinder the development of a strong reading culture. The Community Service Program (KKN) of Universitas Cipasung introduced a solution through the Sahabat Buku (Book Friends) Program and Free Book Stalls as initiatives to foster reading interest and expand literacy access. The methods employed include literacy socialization, group discussions, and the provision of reading materials relevant to community needs. The results indicate increased reading motivation, greater student participation in discussions, and the establishment of shared literacy spaces that engage all levels of society. This program demonstrates that literacy is not merely an individual activity but can be transformed into a joyful, interactive, and educational social experience. Therefore, the Sahabat Buku Program is expected to serve as a foundation for building a sustainable literacy ecosystem in rural communities.